FAKTOR-FAKTOR SISTEM INFORMASI PELAYANAN PUBLIK PADA BPJS KESEHATAN KOTA PALEMBANG - Venny Yusiana (Universitas Batanghari Jambi, 2017)
Information technology to be adopted as a form of public service which gives ease various aspects of business. The research objective is to identify factors important in public services in health BPJS the city of Palembang. While to improve the quality of public services demanded participation of an active and effective role of government in providing information to the public. Obtained from several previous studies the conceptual framework related to public service. The literature review is one way to review the trends that emerged at that time by conducting a systematic review. In this conceptual framework developed based on the study of literature that offer section with public service delivery. Based on the conceptual framework showing the delivery of quality information, user orientation and delivery of service is an important factor in evaluating the information system on public services.Keywords: Public service, BPJS in Health,